Connecting Disasters and Climate Change to the Humanitarian-Development-Peace Nexus. Issue 3 (December 2022) - Mena, Rodrigo; Brown, Summer; Peters, Laura E. R.; Kelman, Ilan; Ji, Hyeonggeun
As climate change increasingly affects the world, much is said about the rising amounts of aid required to support emergency response, long-term development to adapt, and peacebuilding to ensure that conflict does not undermine these efforts. Bringing these ideas together, some advocate for the addition of a separate climate change stream into the humanitarian, development, and peace/peacebuilding nexus (or triple nexus). Based on a critical literature review and synthesis, this article articulates and conceptualizes how climate change perspectives and actions should be integrated into the existing streams of the humanitarian, development, and peace/peacebuilding nexus, rather than being added as a separate stream. The analysis shows the risks of adding climate change as a stand-alone stream and advocates for developing long-term strategies that integrate climate change actions into humanitarian, development, and peacebuilding efforts to better serve all three.